2018
DOI: 10.1164/rccm.201710-2150oc
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Decreases Acute Kidney Injury and Stage 3 Chronic Kidney Disease after Cardiac Surgery

Abstract: In patients undergoing multiple valve replacement and prolonged cardiopulmonary bypass, administration of nitric oxide decreased the incidence of acute kidney injury, transition to stage 3 chronic kidney disease, and major adverse kidney events at 30 days, 90 days, and 1 year. Clinical trial registered with ClinicalTrials.gov (NCT01802619).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
3
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 49 publications
2
114
3
13
Order By: Relevance
“…Some ARDS studies indicated that iNO can adversely affect renal function [9]; however, the mechanism is unclear. A recent study showed that the administration of 80 ppm NO gas into the extracorporeal circulation in conjunction with postoperative iNO treatment significantly reduced the occurrence of renal dysfunction after valve replacement surgery [27]. Recently, Hyun-Su et al reported that iNO did not worsen renal function after lung transplantation; nearly half of the patients in that study were administered extracorporeal membrane oxygenation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some ARDS studies indicated that iNO can adversely affect renal function [9]; however, the mechanism is unclear. A recent study showed that the administration of 80 ppm NO gas into the extracorporeal circulation in conjunction with postoperative iNO treatment significantly reduced the occurrence of renal dysfunction after valve replacement surgery [27]. Recently, Hyun-Su et al reported that iNO did not worsen renal function after lung transplantation; nearly half of the patients in that study were administered extracorporeal membrane oxygenation [28].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AKI is based on two functional markers, an increase of serum creatinine and a reduction of urinary excretion. Predictors of perioperative AKI in patients undergoing heart surgery include preoperative creatinine level, endstage renal disease, 2-2 phenotype of haptoglobin, advanced age, diabetes mellitus, congestive heart failure, generalized atherosclerosis, cardiovascular collapse, nitric oxide, cyanotic heart disease, duration of surgery and elevated postoperative lactate level [4][5][6][7][8][9]. In patients with severe AKI, oliguria and fluid accumulation, renal replacement therapy is the basic method of treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the main target of iNO is lung and pulmonary circulation. In addition, iNO effects on remote organs, such as the kidney [47], liver [48,49], heart [50], and muscle [51], have been investigated, with iNO shown to ameliorate inflammation and ischemia-reperfusion injury.…”
Section: Clinical Effects Of Inomentioning
confidence: 99%